Legal, Regulatory, and Economic Dimensions of Poverty Alleviation Strategies in Brunei Darussalam: An Examination towards Achieving the Global SDGs - Nehaluddin AHMAD; Zheimie H. Zamri; Abdul Hakim Iskandar (Communications of International Proceedings, 2024)
Efforts to combat poverty have posed a persistent challenge globally, impacting societies and governance throughout history. In Brunei, poverty reduction strategies are aligned with the country's Vision 2035 and the Sustainable Development Goals (SDGs). This study aims to examine the legal, regulatory, and economic dimensions of poverty alleviation, as well as investigate the challenges faced by Brunei in implementing these strategies and offer recommendations. Using a qualitative research framework, this study employs document analysis and observational methods to delve into the implementation of poverty reduction strategies. Drawing from various sources such as academic literature, reports, and official documents, we assess the suitability of these strategies for Brunei's Vision 2035 and the SDGs. The key findings highlight both the strengths and limitations of current approaches, providing valuable insights for policymakers and stakeholders. Ultimately, this research seeks to raise awareness and understanding of poverty dynamics in Brunei, contributing to the ongoing discourse on effective socio-economic development strategies.
Keywords: Poverty Alleviation; Sustainable Development Goals (SDGs); Brunei Darussalam.